Alfaxalone and Dexmedetomidine as an Alternative to Gas Anesthesia for Micro-CT Lung Imaging in a Bleomycin-Induced Pulmonary Fibrosis Murine Model - Ferrini, Erica; Mecozzi, Laura; Corsi, Luisa; Ragionieri, Luisa; Donofrio, Gaetano; Stellari, Franco Fabio (Frontiers in Veterinary Science, 2020)
Micro-CT imaging could be considered a powerful non-invasive tool for accessing pulmonary fibrosis in mice. However, the choice of the anesthesia protocol plays a fundamental role to obtain robust and reproducible data, avoiding misinterpretations of the results. Inhaled anesthesia is commonly used for micro-CT lung imaging, but sometimes the standardization of the protocol may be challenging for routine activities in drug discovery. In this study we used micro-CT to evaluate the effects of two anesthetic protocols, consisting in Alfaxalone and Dexmedetomidine mixture, as injectable agents, and gaseous isoflurane, on vehicle and bleomycin-treated mice. No significant differences were highlighted between the protocols either for lung aeration degrees by micro-CT or histologic analyses in both the controls and bleomycin-treated groups. Our results support Alfaxalone and Dexmedetomidine mixture as a suitable and safe alternative compared to isoflurane for lung imaging. We also concluded that this injectable mixture may be applied for several imaging technologies and on different mice models.